PENGARUH PEMBERIAN SEDUHAN JAHE MERAH TERHADAP HIPEREMESIS GRAVIDARUM IBU HAMIL TRIMESTER I - Yovi Nedia Fitra (Universitas Fort de Kock Bukittinggi, 2023)
Nausea and vomiting in pregnancy / Emesis Gravidarum is a common complication during pregnancy caused by increased levels of the hormones estrogen and progesterone produced by Human Chorionic Gonadotropin (HCG) in the placenta. Emesis gravidarum under normal circumstances does not cause many negative effects on pregnancy and the fetus, it's just that if emesis gravidarum is sustained and not treated it can turn into hyperemesis gravidarum which can increase the risk of pregnancy disorders. This research was conducted at the Padang Panjang City Hospital. The design of this study was a quasi-experimental design with Pretest-Postest with Control Group, a sample of 10 pregnant women who experienced hyperemesis gravidarum which were divided into 2 groups, namely intervention and control. The intervention group was given 250 mg of red ginger which was processed into a red ginger steeping drink for 7 days. Data analysis used t-dependent statistical test. The average frequency of pretest nausea was 19.00 times and the pretest vomiting was 12.40 times (intervention), the average frequency of pretest nausea was 19.20 times and the pretest vomiting was 14.00 times (Control). The average frequency of post-test nausea was 6.20 times and post-test vomiting was 2.60 times (intervention), the average post-test nausea frequency was 11.20 times and posttest vomiting was 6.60 times (Control). The difference in the average frequency of nausea and vomiting in the intervention group and the control group was 5.0 (nausea) with p = 0.013 and 4.0 (vomiting) with p = 0.025. It can be concluded that the frequency of nausea and vomiting in the intervention group decreased faster than the control group. The conclusion of this study is that red ginger steeping can reduce the frequency of nausea and vomiting in first trimester pregnant women who experience hyperemesis gravidarum. Keyword : Nausea, Vomiting, Hyperemesis Gravidarum, Red Ginger